Sensors for Automotive and Aerospace Applications - Bhattacharya, Shantanu; Agarwal, Avinash Kumar; Prakash, Om.; Singh, Shailendra; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This volume covers the various sensors related to automotive and aerospace sectors, discussing their properties as well as how they are realized, calibrated and deployed. Written by experts in the field, it provides a ready reference to product developers, researchers and students working on sensor design and fabrication, and provides perspective on both current and future research.
Functional Films for Gas Sensing Applications -- Corrosion sensors for aircraft health monitoring -- Application of Piezoelectric Sensors for Smart Aircraft Structures- Gas sensors for automotive applications -- Sensors for flight/aerospace engineering - basics to advancement -- Sensors in Electric Vehicles- Fabrication processes for sensors for automotive applications -- Sensors in Body Engineering- For teardown and benchmarking processes -- Embedded Sensors for health monitoring of Buzz interconnects in aircraft- A future perspective -- Leakage monitoring in Inflatable space antennas- A perspective to sensitive detection of Helium and Nitrogen gases -- MEMS sensors for automotive applications.
Keywords: Electronic circuits; Transportation engineering; Traffic engineering; Automotive engineering; Aerospace engineering; Astronautics; Electronic Circuits and Systems; Transportation Technology and Traffic Engineering; Automotive Engineering; Aerospace Technology and Astronautics